PLASTIC POLLUTION AND ITS ALTERNATIVES - Lignos, Antonis; Karavasiliadis, Nikitas (Open Schools Journal for Open Science, 2025)
Plastic pollution has become a global environmental crisis. Each year, millions of metric tons of plastic enter the ocean, threatening marine ecosystems and human health. Plastic, being non-biodegradable, accumulates and breaks down into harmful microplastics and nanoplastics. These particles contaminate ecosystems and food chains. This presentation explores the scale and effects of plastic pollution, and it examines sustainable alternatives such as bamboo, paper, and glass. Furthermore, the economic benefits of transitioning away from plastic are also discussed.